How Early Experiences in Cognitive Development Improve Working Memory and Processing Speed Skills of Children - Dube, Heather; Sarette, Sarah (Journal of the American Academy of Special Education Professionals, 2020)
Providing the support that children need to build cognitive skills (i.e. working memory and processing speed) has come to the forefront for special educators today. This study investigated how fourth-grade students within an experimental classroom (N=14) and special education students within a small group setting (N=9) improved their working memory and processing speed through a self-designed board game. Board game activities were conducted for three months. Data were collected from 14 heterogeneously grouped students in an experimental classroom (N=22) and student within a small group setting in the special education classroom setting (N=9). The effects of working memory and processing speed interventions were administered through individual pre- and post- standardized measures. Descriptive statistics for post-test student assessments show no statistical significance in working memory and processing speed. The results of this study suggest that a short-term intervention to increase working memory and processing speed is not impactful. Longer interventions may prove to be more successful and should be examined.